Green HRM and the Power of Well-being: Driving Sustainable Employee Performance - Orabi, Amira Abdelsattar Mohamed; Sudiro, Achmad; Azzuhri, Misbahuddin; Oraby, Ghada Abd Elsattar Mohammed; Khalil, Abdelmajid Idris Mohammed (Jurnal Aplikasi Manajemen, 2025)
Sustainability has become a central concern for organizations, particularly higher education institutions, seeking to achieve long-term performance across economic, social, and environmental dimensions. This study examines the influence of Green Human Resource Management (GHRM) on employees’ sustainable performance, emphasizing the mediating role of employee well-being and the moderating role of gender, with a focus on staff at Brawijaya University. Using a descriptive quantitative approach, data were collected through an online questionnaire, yielding 103 valid responses analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that GHRM has a positive and significant effect on employee well-being but does not have a direct and significant impact on sustainable performance. However, employee well-being has a strong, significant positive effect on sustainable performance and mediates the relationship between GHRM and sustainable performance. This indicates that GHRM enhances sustainable performance indirectly by improving employee well-being, highlighting the strategic importance of human-centered sustainability practices. Furthermore, multi-group analysis shows no significant gender-based differences in the structural relationships, suggesting that both male and female employees respond similarly to GHRM initiatives. Overall, the study underscores that the effectiveness of GHRM depends on its ability to foster employee well-being, which serves as the key mechanism translating green HR practices into sustainable performance outcomes in higher education institutions.